AI-Based Booking Doctor Appointment for Holistic Health Care - Kumar, Tamil Murugan; Sulaiman, Nur Liyana (Applied Information Technology And Computer Science, 2024)
AI-Based Booking Doctor Appointment For Holistic Health Care helps to tackle the difficulties in booking doctor appointment faced by holistic health care which located at Semenyih, Selangor. Currently, there are problem focuses on existing booking doctor appointment processes, such as the manual creation of reports, the informal patient registration process, and appointment scheduling delays caused by diagnosis procedures. To overcome these problem, three objectives have been formulated; to design the system using object-oriented approach, develop a web-based booking doctor appointment, to test the system using user acceptance testing. The waterfall model was applied. The integration of AI image enhancement helps to overcome appointment delays. The combination of PHP and MySQL together with Convolutional Neural Network used to develop this project which enhance iris image for pre-diagnosis procedure. The future works focuses to enhance the performance of the image enhancement to ease the booking doctor appointment of the process.